Diagnostic accuracy of the partograph alert and action lines to predict adverse birth outcomes: a systematic review - Bonet, M (BJOG, 2019)
BACKGROUND: There are questions about the use of the ‘one‐centimetre per hour rule’ as a valid benchmark for assessing the adequacy of labour progress. OBJECTIVES: To determine the accuracy of the alert (1‐cm/hour) and action lines of the cervicograph in the partograph to predict adverse birth outcomes among women in first stage of labour. SEARCH STRATEGY: PubMed, EMBASE, CINAHL, POPLINE, Global Health Library, and reference lists of eligible studies. SELECTION CRITERIA: Observational studies and other study designs reporting data on the correlation between the alert line status of women in labour and the occurrence of adverse birth outcomes. DATA COLLECTION AND ANALYSIS: Two reviewers at a time independently identified eligible studies and independently abstracted data including population characteristics and maternal and perinatal outcomes. MAIN RESULTS: Thirteen studies in which 20 471 women participated were included in the review. The percentage of women crossing the alert line varied from 8 to 76% for all maternal or perinatal outcomes. No study showed a robust diagnostic test accuracy profile for any of the selected outcomes. CONCLUSIONS: This systematic review does not support the use of the cervical dilatation over time (at a threshold of 1 cm/h during active first stage) to identify women at risk of adverse birth outcomes. TWEETABLE ABSTRACT: Alert line of partograph does not identify women at risk of adverse birth outcomes.